Pesticide Labeling: First Aid Statements - Frederick M. Fishel (EDIS)
This document explains first aid statements seen on pesticide labels and discusses the toxicity criteria used in determining the manner in which they are presented on the pesticide label. Examples of typical statements regarding first aid found on pesticide labels are provided. This document is PI-98, one of a series of the Agronomy Department, UF/IFAS Extension. Original publication date February 2006.